Local vulnerability, Forest communities and Forestcarbon conservation: case of southern Cameroon - Chia, E.L.; Somorin, O, Sonwa, D.J; Tiani, A.M. (Academic Journals, 2013)
The mechanism for reducing carbon emissions through forest conservation is dominating climate policy processes in many tropical forests countries. However, there are concerns about the implications of these activities on forest-dependent communities, who are vulnerable to climatic stresses. Reconciling local vulnerability, adaptive capacity and forests carbon conservation initiatives is necessary but challenging. This paper examines this option in two community forests carbon conservation projects in Nomedjoh and Nkolenyeng in southern Cameroon. Base on community perception, the study reveals firstly, that communities are vulnerable to local climate variability and the carbon conservation projects might further exacerbate community vulnerability. Secondly, local adaptation needs and options encompass improvement in livelihood diversification, strengthening the viability of local economic activities, knowledge and capacity building in local agriculture systems and alternative livelihood options. Thirdly, the motivation, incentives and willingness of forest communities to participate in forests conservation activities are somehow influenced by factors linked to their adaptation needs, in addition to the perception of tenure security. Furthermore, the carbon project objectives and activities have prospects to enhance the adaptive capacity of forest communities if well implemented. This study concludes that assessing the vulnerability of livelihood options of communities to both climatic and non climatic stresses is a point of departure to minimise risk on forests carbon conservation schemes.